Crisis in Agricultural Marketing in India - Padmanabhan, S. (International Journal of Bio-resource and Stress Management, 2023)
The history of Indian agriculture is replete with initiatives dating to way back as 1904 in trying to address the issue of credit and much later around the late 1960s, the issue of production and productivity. Soon after independence, India was primarily a food deficient nation, marketable surplus or efforts to provide appropriate prices to farmers, never occupied the mindspace. The efforts at improving production and productivity popularly called the Green Revolution, started and the late ‘60s achieved its objectives and towards later part of ‘70s and early ‘80s, India became self-sufficient in food. Even then, very little effort was made to address the issue of agricultural marketing. After the reforms initiatives of 1990s which was preceded by an Agricultural Debt Waiver Scheme, agricultural credit remained stagnant. Towards the later part of 1990s, the agricultural credit started improving and focus on agricultural marketing by the Government was largely hinged around creating infrastructure for agricultural marketing / storing and grading. Such an approach facilitated the traders, the big farmers and the agro-processors…….